2020
DOI: 10.1089/neu.2019.6540
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Injury Results in Chronic Mechanical Stiffening

Abstract: Gliosis and fibrosis after spinal cord injury (SCI) lead to formation of a scar that is thought to present both molecular and mechanical barriers to neuronal regeneration. The scar consists of a meshwork of reactive glia and deposited, cross-linked, extracellular matrix (ECM) that has long been assumed to present a mechanically ''stiff'' blockade. However, remarkably little quantitative information is available about the rheological properties of chronically injured spinal tissue. In this study we utilize atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 58 publications
(100 reference statements)
1
21
0
Order By: Relevance
“…These differences were not statistically significant (Figure 7B). This indicates that normal SCPC tissue stiffness was spatially relatively homogeneous with low variation in elastic values, which is consistent with past findings (Cooper et al, 2020). The stiffness of regions one and two did not differ significantly across specimens (p ≥ 0.05, Supplementary Figure S4, Supplementary Table S5).…”
Section: Elastic Modulus Of the Rat Spinal Cord And Pia-arachnoid Com...supporting
confidence: 91%
See 1 more Smart Citation
“…These differences were not statistically significant (Figure 7B). This indicates that normal SCPC tissue stiffness was spatially relatively homogeneous with low variation in elastic values, which is consistent with past findings (Cooper et al, 2020). The stiffness of regions one and two did not differ significantly across specimens (p ≥ 0.05, Supplementary Figure S4, Supplementary Table S5).…”
Section: Elastic Modulus Of the Rat Spinal Cord And Pia-arachnoid Com...supporting
confidence: 91%
“…Although numerous studies found that gray matter was stiffer than white matter (Prange and Margulies, 2002;Christ et al, 2010;van Dommelen et al, 2010;Koser et al, 2015), others found the opposite (Ozawa et al, 2001;Kruse et al, 2008;Budday et al, 2015), whereas others observed no significant differences in the moduli of white and gray matter (Maikos et al, 2008b;Finan et al, 2012). This was a challenging question to answer because of the high complexity of neural tissue with anisotropic and inhomogeneous mechanical properties (Koser et al, 2015;Cooper et al, 2020). Furthermore, different experimental techniques had unique strengths and limitations and operated at divergent length scales (Budday et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to other parts of the body where scar tissue is traditionally stiffer than the surrounding healthy tissue [28,29], recent data have indicated that CNS tissue may in fact soften after injury but display increased viscosity [30,31]. Whether these softening changes are retained over time remains unclear though, and chronic CNS injury may still be associated with tissue stiffening [32].…”
Section: Main Textmentioning
confidence: 99%
“…Specifically, the survival rate of the transplanted stem cells is very low due to severe inflammatory responses or other factors in the injured microenvironment [ 10 12 ]. Additionally, the scar-forming gliosis prevents the integration, differentiation, and axon outgrowth of grafted stem cells in the lesion area [ 13 , 14 ]. Moreover, there are also still some concerns regarding the safety of these cells [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%